2023
DOI: 10.1093/biolre/ioad110
|View full text |Cite
|
Sign up to set email alerts
|

Research progress of the Fanconi anemia pathway and premature ovarian insufficiency

Jingyu Zhao,
Yixin Zhang,
Wenbo Li
et al.

Abstract: The Fanconi anemia pathway is a key pathway involved in the repair of deoxyribonucleic acidinterstrand crosslinking damage, which chiefly includes the following four modules: lesion recognition, Fanconi anemia core complex recruitment, FANCD2–FANCI complex monoubiquitination, and downstream events (nucleolytic incision, translesion synthesis, and homologous recombination). Mutations or deletions of multiple Fanconi anemia genes in this pathway can damage the interstrand crosslinking repair pathway and disrupt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 172 publications
(210 reference statements)
0
6
0
Order By: Relevance
“…For example, cancer patients who carry mutations in DNA repair genes, for example BRCA1, BRCA2, may be more susceptible to alkylator damage, 37 , 38 , 39 , 40 , 41 , 42 , 43 and patients with variants of DNA repair genes, such as NBN, MCM8/9 likely have elevated risk of infertility and cancer independent of therapy. 14 , 58 , 59 , 60 Repair mechanisms are limited, increasing cytotoxicity and the risk of further mutagenesis. The unique nature of each clinical case highlights the need for a well‐represented cohort for analysis, including heterogeneity with respect to ethnicity and disease state.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, cancer patients who carry mutations in DNA repair genes, for example BRCA1, BRCA2, may be more susceptible to alkylator damage, 37 , 38 , 39 , 40 , 41 , 42 , 43 and patients with variants of DNA repair genes, such as NBN, MCM8/9 likely have elevated risk of infertility and cancer independent of therapy. 14 , 58 , 59 , 60 Repair mechanisms are limited, increasing cytotoxicity and the risk of further mutagenesis. The unique nature of each clinical case highlights the need for a well‐represented cohort for analysis, including heterogeneity with respect to ethnicity and disease state.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, women with NBS, Fanconi anemia or MCM8/9 variants are at greater risk for both POI and cancer development. 14 , 58 , 59 , 60 For men, it was found that the ERCC1 gene, which is associated with glioblastoma and oral squamous cell carcinoma cancer, was significantly associated with azoospermia. 21 In addition, the inactivation or sub‐function of GPRC6A, which is associated with prostate cancer, was reported to lead to low sperm counts in adulthood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its interaction with BARD1 promotes the phosphorylation of p53 by ATM, leading to the transcription of p21 and cell cycle arrest in the G1 phase. Through its interaction with BRIP1 (also known as FANCJ) [ 45 , 46 ] and DNA topoisomerase 2-binding protein 1 (TOPBP1), BRCA1 facilitates CHK1 phosphorylation by ATM. Phosphorylated CHK1 activates WEE1 and inhibits M-phase inducer phosphatase 1–3 (CDC25A-C).…”
Section: Brcamentioning
confidence: 99%
“…BRCA2 is mainly involved in DNA repair through HR but is also involved in intra-strand crosslinks (ICLs) [ 46 ] and programmed DSBs during meiosis. Moreover, it has also been shown that BRCA2 is involved in the protection of telomere integrity and stalled replication fork degradation.…”
Section: Brcamentioning
confidence: 99%